Rancang-bangun prototipe mesin CNC laser engraving dua sumbu menggunakan diode laser - M Munadi; Aulia Syukri; Joga Dharma Setiawan; Mochammad Ariyanto (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
The development of industrial technology can help the manufacturing industry for producing quality products. One tool that can help produce such quality products is CNC machines. As we know that the price of CNC machines is not cheap. Therefore, in this article, the researchers suggest how to design a prototype CNC laser engraving machine for the acrylic workpiece. The machine is designed as cheaply as possible but provide great benefits. The machine frame is designed using aluminum extrusion, the laser uses a laser diode type, the actuators of axis uses the stepper motor, and the control software uses a USB CNC controller. The dimension of workpiece that can be machined is 600 mm x 300 mm x 2 mm. The optimization of the stepper motor movement system is chosen 1/8 micro stepping after testing full-step method, half-step, 1/8 micro stepping, and 1/16 micro stepping. Using a 2.5 watt diode laser module, the radiant heat received by the acrylic workpiece during the engraving process is 558.8 x 10-5 cal/sec.